An integral membrane constitutively active heparanase enhances the tumor infiltration capability of NK cells - Sofia Liborio-Ramos; Isaac Quiros-Fernandez; Neta Ilan; Soaad Soboh; Malik Farhoud; Ruken Süleymanoglu; Michele Bennek; Sara Calleja-Vara; Martin Müller; Israel Vlodavsky; Angel Cid-Arregui (OncoImmunology)
Eradication of cancer cells by the immune system requires extravasation, infiltration and progression of immune cells through the tumor extracellular matrix (ECM). These are also critical determinants for successful adoptive cell immunotherapy of solid tumors. Together with structural proteins, such as collagens and fibronectin, heparan sulfate (HS) proteoglycans are major components of the ECM. Heparanase 1 (HPSE) is the only enzyme known to have endoglycosidase activity that degrades HS. HPSE is expressed at high levels in almost all hematopoietic cells, which suggests that it plays a relevant role in immune cell migration through solid tissues. Besides, tumor cells express also HPSE as a way to facilitate tumor cell resettlement and metastasis. Therefore, an increase in HPSE in the tumor ECM would be detrimental. Here, we analyzed the effects of constitutive expression of an active, membrane-bound HPSE on the ability of human natural killer (NK) cells to infiltrate tumors and eliminate tumor cells. We demonstrate that NK cells expressing a chimeric active form of HPSE on the cell surface as an integral membrane protein, display significantly enhanced infiltration capability into spheroids of various cancer cell lines, as well as into xenograft tumors in immunodeficient mice. As a result, tumor growth was significantly suppressed without causing noticeable side effects. Altogether, our results suggest that a constitutively expressed active HSPE on the surface of immune effector cells enhances their capability to access and eliminate tumor cells. This strategy opens new possibilities for improving adoptive immune treatments using NK cells.